2019
DOI: 10.1111/bjep.12305
|View full text |Cite
|
Sign up to set email alerts
|

Metacognition and emotional regulation in children from 8 to 12 years old

Abstract: BackgroundThe Metacognitive Affective Model of SRL (MASRL) considers the relationships between metacognition, motivation, and affect. Notably, it provides a theoretical framework to understand how subjective experiences (metacognition and affect) change self‐regulation from a top‐down to a bottom‐up process and vice versa.AimsThe study examines the link between metacognition and emotional regulation in the everyday problem‐solving performance of children in elementary school. Emotional regulation is studied fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…As argued by Semerari et al (2012), emotional understanding and cognitive attribution are essential components of the metacognitive system, which includes identifying and controlling inner emotions, adjusting one's emotions to positively deal with challenges, and reasonably attributing learning results (Schraw, 1998). Naturally, the use of metacognitive strategies is conducive to regulating and managing emotion in the learning process to reduce burnout levels (Seibert et al, 2017;Pennequin et al, 2020). In addition, it has been demonstrated that the improvement of metacognitive awareness can lead to a significant reduction in a negative state of mind (Matthews et al, 1999;Al-Baddareen et al, 2015;Saricam, 2015;O ¨z, 2016), including learning burnout.…”
Section: The Potential Mediating Effect Of Chemistry Learning Burnoutmentioning
confidence: 99%
See 1 more Smart Citation
“…As argued by Semerari et al (2012), emotional understanding and cognitive attribution are essential components of the metacognitive system, which includes identifying and controlling inner emotions, adjusting one's emotions to positively deal with challenges, and reasonably attributing learning results (Schraw, 1998). Naturally, the use of metacognitive strategies is conducive to regulating and managing emotion in the learning process to reduce burnout levels (Seibert et al, 2017;Pennequin et al, 2020). In addition, it has been demonstrated that the improvement of metacognitive awareness can lead to a significant reduction in a negative state of mind (Matthews et al, 1999;Al-Baddareen et al, 2015;Saricam, 2015;O ¨z, 2016), including learning burnout.…”
Section: The Potential Mediating Effect Of Chemistry Learning Burnoutmentioning
confidence: 99%
“…In addition, the 95% CI of the conditional indirect effects of chemistry learning burnout did not include 0, showing that chemistry learning burnout had a significant mediating effect between metacognition and chemistry identity (b = 0.09). The development of metacognitive awareness can help students immediately perceive, understand and adjust their negative emotions to effectively reduce their sense of burnout in the process of chemistry learning (Seibert et al, 2017;Pennequin et al, 2020). An increase in learning burnout causes students to lose interest in learning and fail to perceive the meaning of learning (Hu and Yeo, 2020), affects students' identity processing style, and has a negative impact on students' selfperception of academic ability (Erentaite et al, 2018;Verhoeven et al, 2018); thus, chemistry learning burnout negatively predicts students' chemistry identity (Verhoeven et al, 2018).…”
Section: The Relationship Between Metacognition and Chemistry Identitymentioning
confidence: 99%
“…Organizational strategies include deep processes in the use of various tactics such as taking notes, drawing diagrams, or charts to organize subject matter in several ways. Strategy to regulate metacognition two things need to be examined related to metacognition, namely metacognitive knowledge and regulation (Pennequin et al, 2020;Woolfolk, 2008).…”
Section: Self-regulated Learningmentioning
confidence: 99%
“…2. Demuestran que la metacognición es un predictor significativo del desempeño de los niños en la resolución de problemas (Aurah et al, 2011;Howard et al, 2001;Marić y Sakač, 2018;Özcan y Gümüs, 2019;Pennequin et al, 2019). 3.…”
Section: Metacognición Y Resolución De Problemas En Niñosunclassified